Trans‐oceanic remote power hardware‐in‐the‐loop: multi‐site hardware, integrated controller, and electric network co‐simulation. Issue 18 (7th November 2017) - Lundstrom, Blake; Palmintier, Bryan; Rowe, Daniel; Ward, John; Moore, Tim
Abstract : Electric system operators are increasingly concerned with the potential system‐wide impacts of the large‐scale integration of distributed energy resources including voltage control, protection coordination, and equipment wear. This prompts a need for new simulation techniques that can simultaneously capture all the components of these large integrated smart grid systems. This study describes a novel platform that combines three emerging research areas: power systems co‐simulation, power hardware in the loop (PHIL) simulation, and lab–lab links. The platform is distributed, real‐time capable, allows for easy internet‐based connection from geographically‐dispersed participants, and is software platform agnostic. The authors demonstrate its utility by studying real‐time PHIL co‐simulation of coordinated solar photovoltaic (PV) firming control of two inverters connected in multiple electric distribution network models, prototypical of US and Australian systems. The novel trans‐pacific closed‐loop system simulation was conducted in real time using a power network simulator and physical PV/battery inverter at power at the National Renewable Energy Laboratory in Golden, CO, USA and a physical PV inverter at power at the Commonwealth Scientific and Industrial Research Organisation's Energy Centre in Newcastle, NSW, Australia. This capability enables smart grid researchers throughout the world to leverage their unique simulation capabilities for multi‐site collaborations that can effectively simulate and validate emerging smart grid technology solutions.